Quality And Productivity Analysis Of The Putty Dispenser In The Armature Balancing Process - A Fauzi, Abdul Syukur; Balqis, Balqis; Putri, Farika Tono; Herlambang, Yusuf Dewantoro; Khoryanton, Ampala; Satito, Aryo; Nugroho, Wahyu Isti (Politeknik Negeri Lhokseumawe, 2024)
An electric motor is a device that converts electrical energy into mechanical energy. One of its important components is the armature which functions as the center of movement. Armature is paired with another component of electric motor. In order to achieve a good quality of electric motor, armature quality must be controlled through a standard experiment called balancing test. An adhesive material called putty will be added into armature if the balancing test result is not up to standard. This study conducted in one of automotive industry in Indonesia. The company face a problem in balancing test process. Putty addition carried by factory workers only based on their estimation, resulting in the mass of putty used not in accordance with predetermined standards and also inconsistent, so that the balancing process takes a long time. This research offer a solution for the problem, i.e. putty dispenser to replace the manual putty-picking process with a standardized semi-automatic one. The research objective is to analyze the quality and productivity of the putty dispenser tool design in the armature balancing process. Through 100 armature samples consist of type A and type B, this study examines the quality of the putty mass provided using the most frequently occurring value and uses the independent T-test method to examine the hypothesis that there is a real difference in cycle time before and after the putty dispenser tool. Frame strength testing was also carried out using Solidworks software simulation with 632 N loading. The results of the research on the putty dispenser tool are that the frame used is proven safe, a decrease in cycle time with a percentage of 34.16%, an increase in productivity of 34.13%, also improved quality through the aspects of %NG reduction of 42.29%, and a standardized and constant putty mass of 100 mg for armature type A and 200 mg for armature type B.